2000
DOI: 10.1002/1097-0142(20001115)89:10<2025::aid-cncr1>3.3.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic colorectal adenocarcinomas with high‐frequency microsatellite instability

Abstract: Assessment of MSI status is an essential step in the genetic characterization of large bowel carcinomas and identifies a subset of tumors with distinct clinical, pathologic, and biologic features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
74
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 0 publications
7
74
0
1
Order By: Relevance
“…Moreover, preliminary data with a limited number of tumour samples indicated a good correlation of CLR with a high density of tumor-infiltrating cytotoxic (CD8 þ ) lymphocytes, supporting the hypothesis that CLR positivity is indeed associated with a cytotoxic antitumoural immune response. As in previous reports, we could show that the presence of a CLR was closely associated with a microsatellite unstable phenotype of colorectal cancer (Gafa et al, 2000). The strong antitumoural lymphoid reaction, which frequently occurs in MSI-H colorectal cancers, is commonly attributed to tumour-specific neopeptides generated during MSI-H carcinogenesis.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, preliminary data with a limited number of tumour samples indicated a good correlation of CLR with a high density of tumor-infiltrating cytotoxic (CD8 þ ) lymphocytes, supporting the hypothesis that CLR positivity is indeed associated with a cytotoxic antitumoural immune response. As in previous reports, we could show that the presence of a CLR was closely associated with a microsatellite unstable phenotype of colorectal cancer (Gafa et al, 2000). The strong antitumoural lymphoid reaction, which frequently occurs in MSI-H colorectal cancers, is commonly attributed to tumour-specific neopeptides generated during MSI-H carcinogenesis.…”
Section: Discussionsupporting
confidence: 84%
“…This result is in accord with that of other investigators. 4,10,14 Although the high incidence of absent hMLH1 expression was reported in poorly differentiated colorectal adenocarcinomas, 14 our results indicated that in poorly differentiated adenocarcinoma, the medullary-type carcinoma is primarily affected as compared with pleomorphictype carcinoma. In view of the histopathological type of tumor, we are the first to describe hypermethylation of the hMLH1 promoter in medullarytype carcinomas.…”
Section: Discussionmentioning
confidence: 60%
“…Thus, these findings indicate that medullary-and pleomorphic-type carcinomas differ not only in their clinicopathologic features but also in their molecular findings and therefore we hypothesize that both types of poorly differentiated adenocarcinomas have different pathways in carcinogenesis. 4,14 Medullary-type carcinomas in the elderly share clinicopathologic and biological features with those occurring in patients with hereditary nonpolyposis colorectal cancer: predominant occurrence in the proximal colon, large-sized tumors, expansive growth, prominent Crohn's-like lymphoid reaction, low incidence of lymph node or hematogenous metastasis, and favorable outcome. 22 Common features are tumor location, histology, and biological behavior while age, gender distribution, and the presence of extra-colorectal primary malignancies are different between the two.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So we were not able to determine whether these tumours showed partly chromosomic instability. MSI positive tumours have particular clinical and histopathological features (Lothe et al, 1993;Thibodeau et al, 1993Thibodeau et al, , 1998Kim et al, 1994;Risio et al, 1996;Rüschoff et al, 1997;Jass et al, 1998;Gafa et al, 2000). In our series, the different features associated with MSI status conformed with the characteristics described in the literature: the presence of a mucinous component, rather poor differentiation, a Crohn's like lymphoid stromal reaction and a trend towards a tumour of a larger size.…”
Section: Molecular and Cellular Pathologymentioning
confidence: 99%